Trojan Horse or Useful Helper? A Relationship Perspective on Artificial Intelligence Assistants with Humanlike Features - Uysal, Ertugrul Behlül; Alavi, Sascha; Bezençon, Valéry (My University, 2022)
Artificial intelligence assistants (AIAs) such as Alexa are prevalent in consumers’ homes. Owing to their powerful artificial intelligence, consumers may perceive that AIAs have a mind of their own, that is, they anthropomorphize them. Past marketing research points to beneficial effects of AIA anthropomorphism for consumers and companies, while potential harmful effects have not been empirically explored. In examining both beneficial and harmful effects, this paper adopts a relationship perspective. Indeed, consumers spend large amounts of time with their AIAs, potentially developing a relationship over time that builds on an exchange of benefits and (psychological) costs. A preliminary survey and user interviews, a field study and a field experiment with AIA users show that AIA anthropomorphism may threaten users’ identity, which disempowers them, creates data privacy concerns and ultimately undermines their well-being. These harmful effects particularly emerge in close, long relationships. The field experiment uncovers three empowering interventions which attenuate harmful effects of AIA anthropomorphism in relationships with consumers. With AI-powered technologies taking larger roles in our daily lives, our research highlights key future directions to investigate the permanent ongoing nature of the consumer–AI relationships.
Keywords: Artificial intelligence assistants . Anthropomorphism . Privacy concern . Social exchange . Smart personal assistants . Empowerment . Mind perception . Smart speakers